The Mythology of Sustainable Development - Sztumski, Wiesław (Problemy Ekorozwoju, 2009)
In this article I present a proposition that around the conception of sustainable development, which cannot be possible to realize without radical changes of the social structure and of the style of the economic thinking, an appropriate ideology and a mythology are increasing. Many myths regarding the sustainable development on which mass are being fed appeared. In fact, the mythology of the sustainable development is an instrument of the light of financial and political elites for ruling the world, for preserving the economy based on the neoclassical economy and on the ideology of the consumerism.